The Influence of Talent Management and Job Satisfaction on Employee Performance - Ridwan, Arifki (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research aims to find out how much influence talent management and job satisfaction have on employee performance. This research took samples from employees working at Bekasi Regency Companies which received 60 respondents. The method used is a quantitative survey research method carried out by distributing questionnaires which include statements regarding talent management issues, job satisfaction and employee performance. The results of this research found that job satisfaction has a significant effect on employee performance and talent management does not have a positive effect. on employee performance.